Antibacterial Activity of Thai Medicinal Plants against Methicillin-resistant Staphylococcus aureus - Mullika Traidej Chomnawang (2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen which causes severe morbidity and mortality worldwide. Seventeen Thai medicinal plants were investigated for their activity against MRSA. Garcinia mangostana was identified as the most potent plant, and its activity was traced to the prenylated xanthone, α-mangostin (MIC and MBC values of 1.95 and 3.91 μg/ml, respectively). © 2008 Elsevier B.V. All rights reserved.